PICEAdatabase: a web database for Picea omics and phenotypic information. (15th August 2019) - Lu, Nan; Zhu, Tianqing; Ouyang, Fangqun; Xia, Yan; Li, Qingfen; Jia, Zirui; Hu, Jiwen; Ling, Juanjuan; Ma, Wenjun; Yang, Guijuan; Zhang, Hanguo; Kong, Lisheng; et al.
Abstract: Picea belongs to the Pinaceae family and is a famous commercial tree species because of its straight trunk and excellent timber traits. Recently, omics have been widely used for fundamental and mechanism studies on Picea plants. To improve the accessibility to omics and phenotypic data and facilitate further studies, we compiled the sequences of 2 chloroplast genomes ( Picea crassifolia and Picea asperata ) and 32 complete omics data sets, including 20 transcriptomes, 4 proteomes, 2 degradomes and 6 microRNAs from P . crassifolia, P . asperata, Picea balfouriana and Picea abies tissues under different treatments, in PICEAdatabase. In addition, phenotypic data on plant growth and wood property traits were collected from two field trials of P . crassifolia . PICEAdatabase also includes useful analysis tools, such as BLAST, DESeq2 and JBrowse, to assist with analyses.